2022
DOI: 10.1055/s-0042-1744123
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Predictors of Functional Outcome in Cortical Venous Sinus Thrombosis

Abstract: Objectives Cerebral venous sinus thrombosis (CVST) has a wide clinical spectrum. Despite favorable prognosis, identifying CVST patients with a possible poor functional outcome can be challenging. This study aims to establish the neurological predictors of outcome in CVST. Materials and Methods We analyzed 70 patients of CVST and categorized them into three groups: Group I with isolated intracranial hypertension; Group II—focal syndrome of neurological deficit; Group III—subacute encephalopathy. Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
3
1
1
Order By: Relevance
“… 26 Hemiparesis was a predictive factor of CVT outcome in our study, which is consistent with the results of numerous studies. 12 , 21 , 25 , 27 , 28 Altered consciousness could predict poor CVT outcome, which is in line with previous reports. 12 , 20 , 22 However, Girot et al.…”
Section: Discussionsupporting
confidence: 91%
“… 26 Hemiparesis was a predictive factor of CVT outcome in our study, which is consistent with the results of numerous studies. 12 , 21 , 25 , 27 , 28 Altered consciousness could predict poor CVT outcome, which is in line with previous reports. 12 , 20 , 22 However, Girot et al.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, demographic characteristics, signs and symptoms, radiological findings, treatment, and outcomes were similar to those reported previously. [2][3][4][5][6][7][8][9][10][11] However, our results showed that 68.5% of the patients with CVT had protein S deficiency, which was higher than that previously reported by Karsy et al 8 (10.7%) and Pan et al 9 (55.5%). We provide two explanations for the difference in the percentage of patients with a protein S deficiency: (a) differences in genetic predispositions, or (b) the protein S level was obtained at the time of CVT diagnosis, before the initiation of anticoagulant treatment; therefore, the lower protein S level might be attributed to the effects of acute thrombosis.…”
Section: Discussioncontrasting
confidence: 79%
“…Patients with CVT with headaches usually did not have impaired consciousness, and according to the study by Aarju et al, headaches in CVT might be associated with isolated intracranial hypertension, which was associated with a good outcome. 11 Further, OCP use induced thrombosis by increasing factor VII, factor X, and fibrinogen levels, which might be associated with the good outcome observed in our study since it is a precipitating factor that can be reversed by stopping OCP use, unlike some kinds of malignancies or genetic prothrombotic factors. Most prognostic factors related to poor outcomes have been described in previous reports, [2][3][4][5][6][7][8][9][10][11]16 except for the duration of the symptoms.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations